PELAYANAN PENDIDIKAN INKLUSIF BAGI TUNANETRA (STUDI KASUS DI IAIN IMAM BONJOL PADANG) - Meri Susanti; Nora Zulvianti (Universitas Islam Negeri Imam Bonjol Padang, 2018)
Blindness is a term for individuals who experience interference in terms of vision and need aids in daily activities, and also to support the educational process. Educational services for blind people in educational institutions are generally referred to as inclusive education. This inclusive education model emphasizes full integration, eliminates the labeling of children with the principle of